Combined Analyses of Chloroplast DNA Haplotypes and Microsatellite Markers Reveal New Insights Into the Origin and Dissemination Route of Cultivated Pears Native to East Asia - Yue, Xiaoyan; Zheng, Xiaoyan; Zong, Yu; Jiang, Shuang; Hu, Chunyun; Yu, Peiyuan; Liu, Guoqin; Cao, Yufen; Hu, Hongju; Teng, Yuanwen (Frontiers in Plant Science, 2018)
Asian pear plays an important role in the world pear industry, accounting for over 70% of world total production volume. Commercial Asian pear production relies on four major pear cultivar groups, Japanese Pear (JP), Chinese White Pear (CWP), Chinese Sand Pear (CSP), and Ussurian Pear, but their origins remain controversial. We estimated the genetic diversity levels and structures in a large sample of existing local cultivars to investigate the origins of Asian pears using twenty-five genome-covering nuclear microsatellite (simple sequence repeats, nSSR) markers and two noncoding chloroplast DNA (cpDNA) regions (trnL-trnF and accD-psaI). High levels of genetic diversity were detected for both nSSRs (HE = 0.744) and cpDNAs (Hd = 0.792). The major variation was found within geographic populations of cultivated pear groups, demonstrating a close relationship among cultivar groups. CSPs showed a greater genetic diversity than CWPs and JPs, and lowest levels of genetic differentiation were detected among them. Phylogeographical analyses indicated that the CSP, CWP, and JP were derived from the same progenitor of Pyrus pyrifolia in China. A dissemination route of cultivated P. pyrifolia estimated by approximate Bayesian computation suggested that cultivated P. pyrifolia from the Middle Yangtze River Valley area contributed the major genetic resources to the cultivars, excluding those of southwestern China. Three major genetic groups of cultivated P. pyrifolia were revealed using nSSRs and a Bayesian statistical inference: a) JPs; b) cultivars from South-Central China northward to northeastern China, covering the main pear production area in China; c) cultivars from southwestern China to southeastern China, including Yunnan, Guizhou, Guangdong, Guangxi, and Fujian Provinces. This reflected the synergistic effects of ecogeographical factors and human selection during cultivar spread and improvement. The analyses indicated that Ussurian Pear cultivars might be originated from the interspecific hybridization of wild P. ussuriensis with cultivated P. pyrifolia. The combination of uniparental DNA sequences and nuclear markers give us a better understanding of origins and genetic relationships for Asian pear groups and will be beneficial for the future improvement of Asian pear cultivars.